Evaluation of hydrolysis–esterification biodiesel production from wet microalgae. (August 2016) - Song, Chunfeng; Liu, Qingling; Ji, Na; Deng, Shuai; Zhao, Jun; Li, Shuhong; Kitamura, Yutaka
Graphical abstract: Highlights: Energy consumption of different microalgae biodiesel production routes is evaluated. Vapor recompression and heat integration are utilized to reduce energy consumption. Energy requirement of hydrolysis–esterification route is reduced to 1.81 MJ/L biodiesel. 3.61 MJ can be saved to produce per liter biodiesel by hydrolysis–esterification route. Abstract: Wet microalgae hydrolysis–esterification route has the advantage to avoid the energy-intensive units ( e.g. drying and lipid extraction) in the biodiesel production process. In this study, techno-economic evaluation of hydrolysis–esterification biodiesel production process was carried out and compared with conventional (usually including drying, lipid extraction, esterification and transesterification) biodiesel production process. Energy and material balance of the conventional and hydrolysis–esterification processes was evaluated by Aspen Plus. The simulation results indicated that drying (2.36 MJ/L biodiesel) and triolein transesterification (1.89 MJ/L biodiesel) are the dominant energy-intensive stages in the conventional route (5.42 MJ/L biodiesel). By contrast, the total energy consumption of hydrolysis–esterification route can be reduced to 1.81 MJ/L biodiesel, and approximately 3.61 MJ can be saved to produce per liter biodiesel.